Happily ever after - Ong, Li Yan (2015)
Happily Ever After, is a brainchild of many months of questioning why each of us make films and if so, why that particular film. As graduating film majors, we realised that we might have been caught up largely in the array of technicalities and major set ups and neglected the fundamentals of film making – a foundation of strong stories, acting and translation of themes. Thus, Happily Ever After is a thesis film that forces us to stay true to the core intentions of what we deemed film making is all about and how it is best represented through the chosen forms. Consisting of a small team, Shaun Neo, Pek Hong Kun and myself, narrative films stood out for all three of us, as we believe stories are brought across the strongest. We also agreed that this thesis film, will be a process where the 3 of us, embark on a challenging journey that will place us out of our comfort zones as directing was never our first choice of roles for either of us.